Studies of Phospholipid Reagents Used in Coagulation I: Some General Properties and Their Sensitivity to Factor VIII - Barrowcliffe, T W; Gray, Elaine (Thrombosis and Haemostasis, 1981)
Some general properties of phospholipid reagents have been studied, particularly in relation to their use in detection and measurement of Factor VIII deficiency. There was wide variation among reagents in their total phospholipid concentration, and in the degree of contamination with tissue factor and oxidation products. Although clotting times of normal and haemophilic plasma were affected by change of phospholipid concentration, presence of oxidation products, and order of addition of reagents, these factors did not appear to influence the efficiency of detection of the Factor VIII defect. The method of activation had a definite influence on sensitivity to Factor VIII deficiency, both the type of activator and the time of activation being important.In Factor VIII one-stage assays, use of different phospholipids with the same substrate plasma gave significant differences in precision, but the estimates of potency of a Factor VIII concentrate against a plasma standard were not significantly different.
Keywords: Phospholipid; Factor VIII; APTT